PRACTITIONER OF COOPERATIVE LEARNING AS PART OF NOVICE TEACHERS’ PROFESSIONAL IDENTITY - Astuti, Puji (TEFLIN Journal, 2016)
This paper identifies challenges that English as a foreign language (EFL) novice teachers in Indonesia may face in developing a professional identity, which, in this paper, refers to becoming a practitioner of cooperative learning. Cooperative learning is a mandated teaching method both in the 2006 and 2013 Indonesian curriculum, and is under the umbrella of Communicative Language Teaching approach that has been adopted by English instruction in Indonesia since 1980s. This approach stresses interaction between language learners and the use of the target language in this interaction. Drawing on four related theories of development of selves (Wenger’s Concepts of Community of Practice, Lave and Wenger’s Concepts of Situat- ed Learning: Legitimate Peripheral Participation, Gee’s Sociocultural Views of Identity, and Holland, Lachicotte, Skinner, and Cain’s Concepts of Identi- ty and Agency in Cultural Worlds), four challenges to the development of the target professional identity are identified: (1) the unavailability of community of cooperative learning practitioners, (2) hegemony vs. identity development, (3) agency in the midst of tensions, and (4) institutional identity vs. professional identity. These interconnected and overlapping challenges suggest novice EFL teachers to possess agency to attain the target identity and suggest teacher education programs to equip their student teachers with knowledge and skills of teacher identity development and agency.